Efek permainan monopoli terhadap penguasaan kosakata penelitian eksperimen pada kelas 7 di SMPN 2 Paninjauan - Putra, Hidayat Rahma (ELP (Journal of English Language Pedagogy), 2024)
The research addressed the problem of inadequate vocabulary mastery among seventh-grade students at SMPN 2 Paninjauan during the 2022/2023 academic year. The monotonous media such as using a dictionary was attributed to factors such as rote memorization and the lack of diverse instructional media. Therefore, monopoly games were selected as a teaching medium to investigate their impact on students' vocabulary mastery. The research employed a quasi-experimental design, and the population comprised 45 seventh-grade students at SMPN 2 Paninjauan for the 2022/2023 academic year. Cluster random sampling was utilized to select a sample of 30 students, with 15 assigned to the experimental group and 15 to the control group. The experimental and control groups were determined through a random draw. The pre-test score averaged 47.33, but it significantly increased to 85 after the intervention. Analysis using an independent samples T-test indicated that monopoly games had a more substantial impact compared to dictionary. The rejection of the null hypothesis (H0) suggested a significant positive effect of using monopoly games as a teaching medium on students' vocabulary mastery in the seventh grade at SMPN 2 Paninjauan for the 2022/2023 academic year. Based on the findings, it is recommended that teachers consider this research when exploring a broader range of teaching media to enhance student engagement in vocabulary learning.